Label‐free liquid biopsy based on urine analysis using surface‐enhanced Raman spectroscopy for noninvasive gastric and breast cancer detection. (21st August 2020) - Lin, Xueliang; Wu, Qiong; Lin, Jinyong; Liu, Xiaokun; Jia, Xianggang; Peng, Min; Lin, Duo; Qiu, Sufang; Feng, Shangyuan
Abstract: Liquid biopsy is currently a nondestructive and convenient cancer screening method, which has attracted the attention of many researchers in the field of biomedicine. Moreover, the diagnostic applications of liquid biopsy based on surface‐enhanced Raman spectroscopy (SERS), as a candidate method, potentially offers opportunities for cancer detection. In this work, we mainly evaluated the influence of Au nanoparticles with different sizes on urine SERS signals and analyzed the urine SERS spectra obtained by gastric cancer patients ( n = 50), breast cancer patients ( n = 43), and healthy volunteers ( n = 48) through the principal component analysis combined linear discriminant analysis (PCA‐LDA). The detection sensitivity for identifying gastric cancer versus healthy, breast cancer versus healthy, and gastric cancer versus breast cancer was 90.0%, 96.0%, and 62.0%, respectively. And the corresponding diagnostic specificities for each combination were 93.8%, 93.8%, and 81.4%, respectively. These results show that urine SERS technology based on Au nanoparticles holds promising potential to be a rapid, noninvasive, and label‐free clinical tool for both gastric and breast cancer detection. Abstract : The combination of SERS technology and PCA‐LDA algorithm was employed as a sensitive, rapid, and label‐free method to identify gastric cancer, breast cancer, and healthy human urine samples.